A study on the effect of fluoride dentifrice on the remineralization of incipient enamel lesion - Alfonso, Arlene Aida B.
A 3x3 mm buccal window was created on 70 non carious premolars. The teeth were treated with lactic acid for 48 hours to create incipient enamel lesion. They were randomly grouped into ten and each group was assigned one dentifrice - there being six dentifrices included in the study, the last ghroup served as the control. The groups were treated with their assigned dentifrice for 5 hours at 37 degrees centigrade in a water bath shaker. After treatment, they were rinsed and placed in a metastable calcium phosphate for 24 hours at 37 degrees centigrade. Sections of the teeth were observed under the polarized light microscope. The results show that all the dentifrices are capable of producing remineralization and that remineralization is directly proportional to the fluoride content of the dentifrice.